StaTips Part IV: Selection, interpretation and reporting of the intraclass correlation coefficient - Perinetti, Giuseppe (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
The intraclass correlation coefficient (ICC) is an index or repeatability that reflects both the degree of correlation and agreement between measurements. The ICC is widely used in orthodontic research for any continuous data set that satisfies assumptions for using the parametric methods. However, the ICC comprises a total of ten different variants not always recognized by researchers, which may give different outcomes. Here, a practical guide to choose the corrected variant of the ICC based on study design, and three different aspects (referred to as ‘model’, ‘type’ and ‘definition’) is provided. Finally, a full example of correct data interpretation and reporting is included.